2019
DOI: 10.5415/apallergy.2019.9.e35
|View full text |Cite
|
Sign up to set email alerts
|

Continued loss of asthma control following epidemic thunderstorm asthma

Abstract: BackgroundEpidemic thunderstorm asthma (ETSA) severely affected Melbourne, Australia in November 2016. There is scant literature on the natural history of individuals affected by ETSA.ObjectiveA multicentre 12-month prospective observational study was conducted assessing symptomatology and behaviors of ETSA-affected individuals.MethodsWe used a structured phone questionnaire to assess asthma symptom frequency, inhaled preventer use, asthma action plan ownership and healthcare utilization over 12 months since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Additionally, 66% of respondents who neither had a prior doctor diagnosis of asthma nor any prior symptoms suggestive of undiagnosed asthma described asthma symptoms over the same period. While these findings are similar to those reported in a previous study [5], our data also suggest that majority of individuals in these subgroups continue to remain symptomatic over the 36-month follow-up period, with less than a third of them reporting a reduction in frequency of their asthma symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, 66% of respondents who neither had a prior doctor diagnosis of asthma nor any prior symptoms suggestive of undiagnosed asthma described asthma symptoms over the same period. While these findings are similar to those reported in a previous study [5], our data also suggest that majority of individuals in these subgroups continue to remain symptomatic over the 36-month follow-up period, with less than a third of them reporting a reduction in frequency of their asthma symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it is known that the likelihood of developing a late asthmatic response is increased with higher doses of inhaled allergen [14]. Subsequently, ETSA has been postulated to constitute a massive small airway allergen challenge inducing persistent airway inflammation with nonspecific bronchial hyperresponsiveness, with resultant loss of asthma control or development of de novo asthma in susceptible individuals [5]. Observations from this study provide further support for this theory with >85% of individuals with previously well controlled asthma, and >60% with no prior diagnosis or symptoms suggestive of undiagnosed asthma, reporting asthma symptoms at 12, 24, and 36 months after the initial ETSA event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ali et al [35] reported cases of near-fatal and fatal asthma caused by storms in Kuwait on December 1 st , 2016; 17 patients were admitted with near-fatal asthma, 93.8% had a previous history of asthma, with an average duration of 9 years, 33.3% reported receiving inhaled corticosteroids from their physician and 93.8% relying only on a short-acting β2-agonist to control their asthma; 68.8% reported being outdoors during the storm and eleven patients were diagnosed with fatal asthma. Foo et al [45] reported, in individuals affected by TA, evidence of continuous loss of asthma control in those with previously well-controlled asthma and persistence of symptoms suggestive of asthma in those without a history or symptoms suggestive of previous asthma, even after 36 months of initial TA. Suboptimal rates of adherence to inhaled preventive and having an asthma action plan may contribute to the risk of asthma exacerbation and susceptibility to future episodes of AT.…”
mentioning
confidence: 99%